Simultaneous determination of epinephrine and dopamine by electrochemical reduction on the hybrid material SiO2/graphene oxide decorated with Ag nanoparticles - Cincotto, Fernando H. [UNESP]; Canevari, Thiago C. [UNESP]; Campos, Anderson M. [UNESP]; Landers, Richard; Machado, Sergio A. S. [UNESP] (Royal Soc Chemistry, 2014)
This paper describes the synthesis, characterization and applications of a new hybrid material composed of mesoporous silica (SiO2) modified with graphene oxide (GO), SiO2/GO, obtained by the sol-gel process using HF as the catalyst. The hybrid material, SiO2/GO, was decorated with silver nanoparticles (AgNPs) with a size of less than 20 nanometres, prepared directly on the surface of the material using N,N-dimethylformamide (DMF) as the reducing agent. The resulting material was designated as AgNP/SiO2/GO. The Ag/SiO2/GO material was characterized by X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) and high-resolution transmission electron microscopy (HR-TEM). A glassy carbon electrode modified with AgNP/SiO2/GO was used in the development of a sensitive electrochemical sensor for the simultaneous determination of epinephrine and dopamine employing electrocatalytic reduction using squarewave voltammetry. Well-defined and separate reduction peaks were observed in PBS buffer at pH 7. No significant interference was seen for primarily biological interferents such as uric acid and ascorbic acid in the detection of dopamine and epinephrine. Our study demonstrated that the resultant AgNP/SiO2/GO-modified electrode is highly sensitive for the simultaneous determination of dopamine and epinephrine, with the limits of detection being 0.26 and 0.27 mu mol L-1, respectively. The AgNP/SiO2/GO-modified electrode is highly selective and can be used to detect dopamine and epinephrine in a human urine sample.